2019
DOI: 10.1111/oik.06086
|View full text |Cite
|
Sign up to set email alerts
|

Parasites and stable isotopes: a comparative analysis of isotopic discrimination in parasitic trophic interactions

Abstract: Stable isotopes are widely used to identify trophic interactions and to determine trophic positions of organisms in food webs. Comparative studies have provided general insights into the variation in isotopic composition between consumers and their diet (discrimination factors) in predator–prey and herbivore–plant relationships while other major components of food webs such as host–parasite interactions have been largely overlooked. In this study, we conducted a literature‐based comparative analysis using phyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 73 publications
2
31
1
Order By: Relevance
“…4), while no statistically significant within-pairings relationships were found for carbon (Supplementary Table 2). Negative scaling of trophic discrimination factors with increased host carbon and nitrogen values has previously been observed for parasite-host, predator-prey and herbivore-plant relationships 12,14,31 and may be associated with dietary quality. In this study, there appears to be an increased spread in the fractionation (Δ 15 N values) observed within the herbivore S. lineatus , with the lowest δ 15 N values occurring with the highest Δ 15 N values and a distinct grouping of individuals with lower Δ 15 N values corresponding with the highest δ 15 N values (Fig.…”
Section: Discussionmentioning
confidence: 60%
See 4 more Smart Citations
“…4), while no statistically significant within-pairings relationships were found for carbon (Supplementary Table 2). Negative scaling of trophic discrimination factors with increased host carbon and nitrogen values has previously been observed for parasite-host, predator-prey and herbivore-plant relationships 12,14,31 and may be associated with dietary quality. In this study, there appears to be an increased spread in the fractionation (Δ 15 N values) observed within the herbivore S. lineatus , with the lowest δ 15 N values occurring with the highest Δ 15 N values and a distinct grouping of individuals with lower Δ 15 N values corresponding with the highest δ 15 N values (Fig.…”
Section: Discussionmentioning
confidence: 60%
“…The relatively uniform neutral or negative relationships for Δ 13 C values across the pairings located from both the dietary tract and the general cavity indicate that lipid carbon is likely utilized to support tissue growth beyond species closely associated with fatty tissues (e.g. blood and liver) 13,14 . This relationship should be examined further with methods that incorporate metabolic pathway techniques for target species beyond model organisms targeted for pathogenicity 21,22 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations